The Challenges of the French Secularism on the Lives of Muslim Women - FARAH, HAMDA ABDOU (İstanbul Kültür Üniversitesi, 2023)
This thesis explores the challenges encountered by Muslim women in France due to secularism, a key principle of French society. By focusing on the complex interactions between secularism, religious identity, and gender, this research examines the tensions and conflicts experienced by Muslim women in their daily lives. The study analyzes French secular policies and laws, including the ban on full-face veiling, and their impact on the rights and freedoms of Muslim women. It also examines the psychological, social, and cultural repercussions of these measures on their sense of belonging and ability to express their religious and cultural identity. Furthermore, this research examines the specific challenges faced by Muslim women in areas such as education, employment, and access to public services due to secularism and the stereotypes and prejudices associated with their religion. The primary objective of this research is to provide an in-depth analysis of the interactions between secularism, gender, and religious identity, this thesis contributes to a better understanding of the challenges faced by Muslim women in France and aims to promote constructive and inclusive dialogue on the issue of secularism in French society.
Fransız Laikliğinin Müslüman Kadınların Yaşamları Üzerindeki Zorlukları
▪ Yüksek lisans tezi.
Keywords: Secularism; Muslim Women; France